Masculinist method: a cautionary tale. (2014) - ,
Abstract : Purpose – This is a cautionary tale. In previous research on male‐to‐female transsexuals, the author's analysis was too knowing, detached, and full of authorial superiority. In other words, it was too masculine. The paper aims to discuss theses issues.Design/methodology/approach – In this paper, the author brings to the fore the deleterious effects of the masculinist method. The author then writes a palinode in order to allow masculinity and male to be performed and un/tethered differently by and on different bodies and different subjects.Findings – The paper concludes with a discussion of how a masculinist method emerged and its consequences.Originality/value – This is a revised look at the author's previous work on the subject. Acknowledgements : The author is grateful to Jennifer Germon not only for this insight, but for all her generous comments on this manuscript.